Assessing Climate Change Adaptation Strategies among Livestock Rearers in Bundelkhand Region, India - Mishra, Gaurav; Gupta, B. K.; Mishra, B.P.; Verma, Arjun P; Mishra, Dheeraj; Shukla, Gaurav (Indian Journal of Extension Education, 2025)
The study was conducted in the year 2024-25, assessing both the degree of implementation of adaptation measures and the factors that influence these strategies among livestock rearers in the Banda district of Uttar Pradesh and Chhatarpur district of Madhya Pradesh. A total of 320 livestock rearers were chosen as respondents using a multi-stage sampling method. Eighteen adaptation strategies were identified using a Climate Change Adaptation Index (CCAI), and subsequently analysed through factor analysis and ordinal logistic regression to ascertain the determinants of adaptation behaviour. Findings revealed that maintaining fodder banks (mean score: 1.825), seasonal livelihood diversification (1.6906), and vector control measures (1.4625), were the most frequently adopted strategies. Conversely, preventive healthcare, low-cost housing improvements, and feeding adjustments reflected lower levels of adoption. Factor analysis identified three components, accounting for 72.22 per cent of the total variation. Ordinal logistic regression showed that herd size, community participation and education levels were favourably correlated with enhanced adaptation, but family size showed negative significance. A majority of respondents (66.87%) exhibited a moderate level of adaptability. The results highlighted the disparate adaptive capacities among livestock rearers and the need for targeted extension interventions in the Bundelkhand region.